Poskusi na živalih v Sloveniji v številkah - Perše, Martina (Zdravniški vestnik, 2008)
Background The use of animals in experiments started in ancient Greece and continued through the centuries in even greater extent. It is estimated that in 1960 worldwide about 30 million vertebrates were used for experimental purposes and in 1970 between 100 and 200 million. Animal use seemed to stabilize during the late 70ćs and started to decrease from the early 80ćs till the begining of the 21st century. Conclusions The aim of this article is to provide a brief overview of the number, species and purpose of animals usedfor experimental and other scientific purposes in Slovenia and worldwide in recent years.
Keywords: Animal Rights; Animals, Laboratory; Blood; Bolezen, živalski modeli; Disease Models, Animal; poskusi na živalih; Slovenia; Slovenija; statistika; zakonodaja; Žival, pravice; Živali laboratorijske